Studi Fenomenologi: Pengalaman Adaptasi Penderita Penyakit Menular Seksual - Ratu Kusuma; Dwi Kartika Pebrianti; Marnila Yesni; Rahmi Dwi Yanti (Universitas Baiturrahim, 2023)
Sexually transmitted diseases (STDs) are one of the causes of health, social and economic problems in many countries, and ± 500 million new cases of STDs occur every year worldwide. STDs are the gateway to HIV infection especially syphilis. Syphilis can increase the risk of contracting HIV up to 300 times. The negative consequences of STDs as infertility, stillbirth, congenital abnormalities and cervical cancer. The purpose of this study was to identify the experience of adaptation of STDs sufferers. A qualitative research with phenomenological approach to 10 participants (2 syphilis patients and 8 HIV/AIDS) which were selected purposively. Data collected using in-depth interview, observations and documentation. Interviews were IMS Clinic and VCT Puskesmas Putri Ayu and HIV/AIDS sufferers communities in Kota Jambi (Yayasan Kanti Sehati Sejati). Data collection on January 13-16 February 2021, personal interviews last 60-75 minutes and concurrent interviews are 75-120 minutes, recorded with a voice recorder. Data were analyzed descriptively through theme analysis, results 7 themes related to the experience of adaptation of STDs sufferers: 1) complaints and physical complications of STDs sufferers; 2) the psychological impact of STDs; 3) STD risk factors; 4) STDs treatment; 5) efforts to prevent recurrence/severity; 6) coping mechanisms for PMS sufferers; and 7) behavioral responses of STDs sufferers: physiological, self-concept, role function and interdependence.